22. A NOVEL, FAST, SINGLE TUBE AMPLIFICATION AND INDEXING APPROACH FOR PGT-A FOR ILLUMINA® SEQUENCING INSTRUMENTS. (August 2019) - Warren, K.; Myers, S.; Tay, L.; Protopsaltis, S.; Jasper, M.
Abstract : Introduction: Most methods to prepare embryo biopsy samples for Preimplantation Genetic Testing for Aneuploidy (PGT-A) for Illumina® sequencing instruments use a two-step approach of Whole Genome Amplification (WGA) followed by library preparation. A single tube, PCR indexing approach offers several advantages for laboratories performing PGT-A including protocol time efficiencies and reduced hands on time. A novel protocol has been developed based on the PerkinElmer DOPlify® WGA kit. The aim of this study was to determine the accuracy and performance characteristics of this protocol on 5 cell samples from euploid, single and double trisomy cell lines. Material and methods: Five-cell samples representative of trophectoderm biopsy were manually sorted from aneuploid cell lines (Coriell Institute) and euploid lymphocytes. Cell lysis and WGA were performed using a modified DOPlify® kit protocol (PerkinElmer) followed by incorporation of Illumina specific adapter sequences and unique indexes in a novel single tube approach. Amplified, indexed cell samples were purified, quantified then pooled before 50 sample multiplex and 1 × 75bp read length sequencing on the Illumina MiSeq® Instrument using v3 chemistry. Sequencing data was analysed for correct aneuploidy calling using the PG-Find™ software (PerkinElmer). Results: A total of 104 multicell samples were processed with the following karyotypes: 47, XY, +15 (n=22), 47, XX, +18 (n=20), 48, XXY, +21 (n=20), 46, XY (n=22) and 46, XX (n=20). Three samples were excluded from final analysis due to weak amplification (3%). All other samples were processed through to sequencing and displayed the expected karyotype when analysed with the PG-Find™ software, with no false positives or false negatives observed. The 50-sample multiplex generated an average of 510, 000 mapped reads per sample with a 98.9% mapping rate to hg19. The novel protocol took on average 4.5 hours (2.5 hours hands on) to process 50 samples from sample receipt to MiSeq® Instrument loading. Conclusions: The novel one tube amplification and indexing method was shown to be a fast, accurate protocol for PGT-A utilising Illumina® sequencing instruments. Sequencing ready, 50 sample multiplex pools were prepared in 4.5 hours, readily enabling a less than 24 hour turn-around time from sample receipt to reporting. Studies processing single cells (representative of blastomere biopsy) and cell samples with smaller segmental aberrations to determine the resolution of the protocol are underway, which will be followed by clinical validation using embryo biopsy samples.